Autonomous operation of hybrid AC-DC microgrids with progressive energy flow tuning - Loh, Poh Chiang (2013)
Modern distributed sources can either be ac or dc. It is thus possible to form hybrid microgrids with ac and dc sub-grids inter-tied by power converters. The resulting hybrid architecture allows loads to be flexibly placed so as to minimize the amount of energy conversion needed and hence its accompanied losses. Hybrid microgrids are therefore more efficient with a control scheme now proposed for controlling them. The scheme allows the hybrid microgrids to operate autonomously without fast communication links, while yet maintaining high efficiency through progressive energy flow tuning. Experimental testing has already been performed with results presented in a later section for verifying the control concepts discussed.